Friday

April 18, 2014

April 18, 2014

Posted by **hokoslavia** on Sunday, March 16, 2008 at 6:18pm.

- math -
**Damon**, Sunday, March 16, 2008 at 6:29pmsame as

f[ g(x) ]

g(-1) = 4(-1) -5 = -9

f(-9) = 3(-9) - 7 = -27 - 7 = -34

**Related Questions**

calc - 6(4x+3)^5(4)(3x-5)^5+ 5(3x-5)^4(3)(4X+3)^6 common factors: (4x+3)^5 (3x-5...

bobpursley,math - about this problem , I figured it out and i did get the answer...

math,bobpursly, - 4x-2x^2+4x^3 from 4x^3+x-3x^2 4x^3+x-3x^2 -( 4x-2x^2+4x^3) ...

mathh - Let f(x)=x+2 Ix-3I and g(x)=3x-1 Find all solutions to the equation f(g(...

math - sums and differences of rational algebraic expression please answer the ...

Math - Find X 27^4x-2=243^3x+6 Please explain how to do it. Thanks 27^(4x-2)=243...

math - find the difference when (-2x^2+7x-5) is subtracted from (3x^2-4x+2). -2x...

Math - Can someone please check my answers below for accurateness? The ...

Find the minimum/maximum - The question is as followed: y=-3x^2 + 4x This is how...

Math/Algebra - Find each sum or difference (3x^2 + 7x- 2)+ (2x^2 - 3x + 4) ...